The Influence of Community Health Cadres' Role and Family Support on Adherence to Iron (Fe) Tablet Consumption Among Pregnant Women - Erni Faturahmah; Uswatun Hasanah; Nurhayati Nurhayati (Jurnal EduHealth, 2025)
According to the World Health Organization (WHO), the global prevalence of anemia is approximately 40% among children aged 6–59 months, 37% among pregnant women, and 30% among women aged 15–49 years. The roles of community health cadres and family support are essential in creating a supportive environment that encourages pregnant women to adhere to iron (Fe) tablet supplementation. This study aimed to examine the influence of community health cadres' role and family support on adherence to iron (Fe) tablet consumption among pregnant women. This research employed a quantitative descriptive design with a cross-sectional approach. The independent variables were the role of community health cadres and family support, while the dependent variable was adherence to iron (Fe) tablet consumption. The study was conducted in Nunggi Village, within the working area of Wera Community Health Center, Bima Regency, West Nusa Tenggara, Indonesia, in 2025. The population and sample consisted of all 32 pregnant women, selected using a total sampling technique. Data were collected using a structured questionnaire and analyzed through univariate and bivariate analyses. The results showed that both the role of community health cadres and family support had a statistically significant influence on adherence to iron (Fe) tablet consumption among pregnant women, with p-values of 0.023 and 0.046, respectively. In conclusion, the roles of community health cadres and family support significantly influence pregnant women's adherence to iron (Fe) tablet consumption. Therefore, strengthening the involvement of community health cadres and enhancing family support are recommended to improve adherence to iron supplementation during pregnancy.